Oldhamianoside inhibits the growth of ovarian cancer both in vitro and in vivo via adjusting inflammation and angiogenesis signals - Li, Zenghui (Onco Targets Ther, 2018)
OBJECTIVE: The aim of this study was to determine the effects and possible mechanisms of oldhamianoside on the growth of human ovarian cancer both in vitro and in vivo. MATERIALS AND METHODS: CCK-8 assay was applied to estimate the effect of oldhamianoside on cell proliferation inhibition in vitro. Nude mice bearing human ovarian SKOV3 xenograft tumors were treated with oldhamianoside to investigate the effects of compound administration on tumor growth in vivo. To further investigate the mechanisms of inhibition effects of oldhamianoside on ovarian cancer growth in vivo, the levels of TNF-α, IL-6, and MCP-1 in plasma from the mice were measured by ELISA. Western blot was used to detect the expression of angiogenesis- and/or apoptosis-related proteins. RESULTS: We found that oldhamianoside treatment inhibited SKOV3 proliferation and growth both in vitro and in vivo. Meanwhile, the levels of TNF-α, IL-6, and MCP-1 in plasma were markedly suppressed in oldhamianoside-treated mice. Additionally, oldhamianoside treatment inhibited the expression of VEGF and VEGFR2 and decreased the expression of caspase-3 and Bax/Bcl-2 ratio. CONCLUSION: Our data indicate that oldhamianoside has an obvious inhibition effect on SKOV3 proliferation, and the mechanisms might be related to inhibition of cell growth, apoptosis induction, and adjusting the inflammatory response and angiogenesis signal.